Anti-neuroinflammatory agents for the treatment of Alzheimer's disease. (September 2013) - Zhou, Wei; Hu, Wenhui
Alzheimer's disease (AD) is complicated and difficult to fully understand, it might need multiple drug-discovery strategies to combat the disease. Regardless of the cause of AD, neuronal death in the brain plays a key role in AD progression and is directly linked to neuroinflammation. Thus, the regulation of neuroinflammatory processes might be a practical strategy for the treatment of AD. This review highlights the development of anti-neuroinflammatory agents that have shown promise in vitro or in vivo by attenuating microglial activation or cognitive decline. The agents are categorized based on the related signaling pathways, including the receptor for advanced glycation end products, p38 MAPKs, NF-κB and peroxisome proliferator-activated receptor γ; and inhibitors against microglial activation lacking clear mechanisms. These anti-neuroinflammatory agents support the concept and represent important chemical probes for the development of anti-neuroinflammatory drugs for the treatment of AD.